Synthesis and synergistic flame‐retardant effects of rigid polyurethane foams used reactive DOPO‐based polyols combination with expandable graphite. Issue 16 (2nd November 2020) - Xu, Jingshui; Wu, Yuqiang; Zhang, Bangling; Zhang, Guoliang
Abstract: Flame retardant rigid polyurethane foams (FR‐RPFs) were prepared by a one‐pot and free‐rise method with reactive DOPO‐based polyols and expandable graphite (EG) as flame retardants. The flame retardancy, thermal stability and morphological of FR‐RPFs were investigated by some characterization testing techniques. Less than 10 wt% EG incorporated in the FR‐RPF‐0 can improve the mechanical strength due to forming a chemical bond between FR‐RPF and EG. With addition of 1.5 wt% P and 12.5 wt% EG, the FR‐RPF achieved the LOI of above 30%, meeting the standard of combustible stage B1 . Thermal stability and residual mass of FR‐RPFs effectively increased as the increase EG by TGA analysis. EG could help to form a more thermally stable and compact char layer during combustion by SEM analysis. Cone calorimeter tests indicated that the obvious synergistic flame‐retardant effects between DOPO‐based polyols and EG could be concluded in FR‐RPFs. The co‐existence of DOPO‐based polyols enabled EG adhere more smoke fragments and the combination of DOPO‐based polyols and EG better strengthened char layer, so as to enhance the barrier and protective effect of residue. The synergistic flame‐retardant effects from the combination system of DOPO‐based polyols/EG endowed themselves with high flame‐retardant efficiency. Abstract :